Binaries and multiple stellar systems - Horch, E. (Planets, Stars and Stellar Systems Volume 4: Stellar Structure and Evolution, 2013)
Binary and multiple stellar systems have importance in three main areas of astronomy and astrophysics. First, because of the relatively simple gravitational interaction at work in the case of binary stars, these systems provide a basic check on stellar structure and evolution theory since the masses may be determined through observation. When these masses can be linked to other properties of the two stars, such as luminosity, color, and radius, they can provide very stringent constraints on stellar models. Second, the statistics of binary and multiple star systems provide clues to star formation mechanisms and environmental effects in the galactic gravitational potential and in clusters. Although a number of good results have been obtained in nearby star clusters and associations, knowledge of the field population has been somewhat limited until recently by a lack of large, complete samples of binaries. However, there appears to be a great deal of promise in this area for the coming decade in part due to astrometric satellites such as Hipparcos and Gaia. Third, the binary scenario is invoked to explain several important types of astrophysical phenomena such as Type Ia supernovae, cataclysmic variables, and stellar x-ray sources. Since the first of these mentioned is a standard candle for the extragalactic distance scale, it may even be said binary stars play a minor role in field of cosmology. However, in this chapter, the focus will mainly be on normal stars in binary and multiple-stellar systems. The basic physics of binaries will be reviewed, and the observational methods in use today will be discussed together with their limitations and prospects for the future. Finally, an overview of the current science in the three main areas mentioned where binaries have a significant impact will be given. © Springer Science+Business Media Dordrecht 2013.
Journal Abbreviation: Planets, Stars and Stellar Systems Volume 4: Stellar Structure and Evolution
Keywords: Astrometric; Binary star orbits; Detached binaries; Interacting binaries; Interferometric; Spectroscopic; Star clusters; Star formation; Stellar astrophysics; Stellar masses; dept.phy